The distributional effects of place-based policies in the EU - Valentin Lang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This chapter examines the distributional effects of place-based policies in the EU. In a first step, it characterizes existing income inequalities in the EU and distinguishes between their interregional and intraregional dimensions. A key result is that inequalities within European regions make an important contribution to overall inequality in the EU. Against this background, the chapter then reviews the economic literature on the effectiveness and distributional effects of place-based policies in general and EU regional policy in particular. The evidence from this literature suggests that while place-based policies can reduce inequalities between regions, they tend to increase inequalities within regions. The chapter concludes with a discussion of policy recommendations for EU regional policy that can be derived from these findings.
Keywords: D31; E24; H72; R11; R23; 330; place-based policies; regional inequality; intraregional inequality; European Union (EU)